PERANCANGAN BUKU ILUSTRASI PENGENALAN NAMA BUAH-BUAHAN DENGAN SISTEM ISYARAT BAHASA INDONESIA (SIBI) BERBASIS KARAKTER UNTUK ANAK-ANAK TKLB-B KARYA MULIA SURABAYA - Setiawan, Leonard; Riyanto, Darwin Yuwono; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Interest illustrated book about the introduction of  fruits name with a character-based system SIBI for children TKLB-B Karya Mulia Surabaya is as a learning medium that contains the values of science. The study was conducted with qualitative methods based on interviews, observation, documentation, and literature to support the design of a book about the house's name recognition fruits. Data can be analyzed at several stages of data reduction, data presentation, and conclusion. After analyzing the data found informative design concept, the average informative Indonesian big dictionary into said. This concept aims to be informative book designed to provide insight to the public about the introduction of fruits name. Mechanical reality promoted expected to help draft informative because it is interactive, so people can find out the name of the fruit in the dictionary SIBI. Results of design book is expected that children know more about the fruit in the form of illustrated book based character Keywords: Book, Illustration, Introduction Name Fruits, Innovative, Character-Based, SIBI System.